Pengaruh Variabel Anteseden Kinerja terhadap Kepuasan Kerja dengan Penilaian dan Kompensasi Sebagai Variabel Moderator (Studi Pada Manajer Bank di Jawa Timur) - Gerrit M. Pentury; Djumilah Zain; Umar Nimran; Armanu Thoyib (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research base on the fact that works performance is an important and challenging for managers. As a result, a manager needs to understand behavior differences and mange them into a positive behavior, called as high performance. This research aims 1) to what extent ability, motivation, and role perception influence perpormance; 2) to what extent ability, motivation, and role perception functioning as three antecedent variables influence job satisfaction; and 3) to what extent appraisal and compensation functioning as moderating variables strengthen the influence of performance on job satisfaction. The explanatory research, analysis unit of this research is middle managers at banks in East Java. This research employed interview with questionnaire model ad observation in collecting the data. In addition, this research utilized Structural Equation Modeling (SEM). This research reveals that (1) ability, motivation, and role perception influence performance; (2) ability, motivation, and role perception functioning as three antecedent variables influenced job satisfaction; (3) performance and performance appraisal functioning as moderating variables strengthened the influence on job satisfaction; however, compensation as a moderating variable did not strengthen the influence of performance on job satisfaction.Keywords: Ability, Motivation, Role Perception, Performance, Performance Appraisal, Compensation, Job Satisfaction